Modelo para avaliação de desempenho do sistema de saúde municipal com foco nas ações da saúde materno-infantil da atenção básica por meio de indicadores sociais - Ferraz, João Antonio Robalinho (2010)
The current work concerns the performance of municipal health systems, focusing on maternal/child healthcare. With the aim of identifying possible weaknesses in health systems, specifically those in which Primary Attention (PA) is the main or exclusive strategy of municipal administration activity, the theoretic model of health indicators named ADS, was created. Applied in cities with populations between 14,000 and 35,000 inhabitants, where the health system is exclusively based on PA policy, this model was constructed using the consensus technique, with the formation of a group of 12 specialists in the area of collective health to define and validate the criteria for analysis of the systems. Tested in the town of Itai, located in the Meridian hinterland, 282 kilometers from the capital of Pernambuco, the ADS indicated below average environmental and socio-economic factors, besides vulnerabilities in maternal/child healthcare which negatively influenced the condition of health in the municipality. The evaluation further verified unsatisfactory performance in terms of child and pre-natal accompaniment through medical appointments (effectiveness); child assistance (continuity); appointment realization for children and pre-natal immunization for mothers (access to Primary Attention services); productivity of the actions performed by health professionals (efficiency) and capacity to investigate infant mortality, quality of registers and pre-natal control of syphilis (health vigilance). A low level of investment in healthcare was also observed, combined with inadequate human resources and material to provide services. At the end of the research, it was possible to identify the viability of the models application in planning